Practical Tips for Facilitating Research - Bent, Moira (Practical tips for library and information professionals, 2016)
This practical guide offers innovative tips and reliable best practice to enable new and experienced library and information professionals to evaluate their current provision and develop their service to meet the evolving needs of the research community.